Teaching biotechnological disciplines in conditions of distance learning - Lavinska, Olena (Problems of Environmental Biotechnology, 2021)
Necessary for improvement of educational process in the conditions of distance learning is the use of modern computer technologies which allow to raise informativeness, illustrativeness and perception of a training material.